Correlation of CD2 binding and functional properties of multimeric and monomeric lymphocyte function-associated antigen 3. - Dustin, M; Olive, D; Springer, T (1989)
LFA-3 was purified with an intact (mLFA-3) or an enzymatically removed membrane-anchoring domain (sLFA-3). Gel filtration and sucrose gradient sedimentation showed sLFA-3 to be a single highly glycosylated polypeptide chain in solution, while mLFA-3 formed micelles of 8 LFA-3 monomers. 125I-mLFA-3 bound to Jurkat T leukemic cell surface CD2 with much higher avidity than sLFA-3. mLFA-3 binding had characteristics of a multivalent interaction with cell surface CD2 and had an avidity of 1.5 nM for Jurkat cells and 12 nM for resting T cells. Two CD2 mAbs tested did not block mLFA-3 binding: 9-1 and CD2.1. These mAbs were tested in combination with LFA-3 for their ability to activate T cells. The combination of mLFA-3 and CD2.1 mAbs induced a rapid increase in cytosolic free Ca2+ in Jurkat cells which was proportional to mLFA-3 occupation of CD2 sites. sLFA-3 showed no activity in the Ca2+ flux assay. The combination of mLFA-3 and the CD2.1 mAbs significantly stimulated proliferation of PBMC. The combination of mLFA-3 and 9-1 mAbs was weakly or not mitogenic for the same cells. The combination of CD2.1 and sLFA-3 at concentrations up to 480 nM was not consistently mitogenic. Therefore, monomeric LFA-3/CD2 interaction appears to have a relatively low affinity, while multimeric LFA-3 binds with high avidity. T cell activation by binding of LFA-3 to CD2 appears to require occupation of 10(4) to 10(5) CD2 sites, which is likely to occur during adhesion, but is rare in receptor systems with soluble ligands.